Tinjauan Filosufis tentang Komponen Manajemen Pendidikan (Tujuan, Kurikulum, Pendidik, Peserta Didik, Metode dan Evaluasi Pendidikan) - Achmad Wahyudin; Nasirudin Nasirudin; Encep Syarifudin (Journal on Education, 2024)
Education is an effort to improve individual quality. This individual improvement process must be accompanied by good preparation and implementation. Therefore, education must be supported by the best components in order to achieve educational goals. Education is an effort carried out by humans for thousands of years. In fact, education took place before humans knew how to read and write. This business aims to improve the comfort of human life. Since thousands of years until now, what can never be separated from the educational process are students. A learning process can be carried out without a (human) teacher. However, it is impossible for the learning process to not have a student. This indicates that learning is basically centered on humans as students. Human readiness to discover knowledge or truth is the force that brings us to a civilization that continues to progress and develop. Nowadays, education must remain serious in providing provisions for humans. Seeing this urgency, there is a gap that we can develop together for students at the junior high school level. In the early stages, teenagers want to determine their identity. The purpose of this research is to examine educational objectives, curriculum, educators, students, methods and evaluation. The method used is a qualitative method with a literature review approach. Data sources were obtained from several books and journals. Research findings show that educational components are elements that will support the achievement of educational goals.